2015
DOI: 10.1080/1360080x.2015.1034425
|View full text |Cite
|
Sign up to set email alerts
|

The current status of teaching staff innovation competence in Ugandan universities: perceptions of managers, teachers, and students

Abstract: How competent are university teaching staff to deliver effectively their present and future university duties in Uganda? This question was explored in this study by collecting data from managers (n = 90), teachers (n = 126), and students (n = 179) through a questionnaire administered at Kyambogo University. The results show that teacher performance in the role of innovating; knowledge society facilitating; collaborating and networking; higher education designing and developing; and entrepreneurship, could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Jena & Sahoo, 2014;Mitchelmore & Rowley, 2010, 2013Taatila, 2010) after testing in educational settings. While studies have recognised the connection between entrepreneurship and innovation (Becherer & Maurer, 1999;Bergh et al, 2011;Bunk, 1994;Szerb, 2003), we found that innovation and entrepreneurship were also linked (Bjornali & Støren, 2012;Cerinšek & Dolinšek, 2009;Chell & Athayde, 2011;Edwards-Schachter et al, 2015;Gundry, Ofstein, & Kickul, 2014;Kasule et al, 2015;Santandreu-Mascarell et al, 2013;Waychal et al, 2011). The fifth area for further research is the different competences in each phase of the innovation process (Standing et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Jena & Sahoo, 2014;Mitchelmore & Rowley, 2010, 2013Taatila, 2010) after testing in educational settings. While studies have recognised the connection between entrepreneurship and innovation (Becherer & Maurer, 1999;Bergh et al, 2011;Bunk, 1994;Szerb, 2003), we found that innovation and entrepreneurship were also linked (Bjornali & Støren, 2012;Cerinšek & Dolinšek, 2009;Chell & Athayde, 2011;Edwards-Schachter et al, 2015;Gundry, Ofstein, & Kickul, 2014;Kasule et al, 2015;Santandreu-Mascarell et al, 2013;Waychal et al, 2011). The fifth area for further research is the different competences in each phase of the innovation process (Standing et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Content knowledge is mentioned as an innovation competency factor in only five studies (Avvisati et al, 2013;Bjornali & Støren, 2012;Jack et al, 2014;Kasule, Wesselink, Noroozi, & Mulder, 2015;Lindfors & Hilmola, 2015). Avvisati et al (2013) used the term subject knowledge, which is understood as a synonym for content knowledge.…”
Section: Content Knowledge and Making Skillsmentioning
confidence: 99%
“…Proactive. Teacher entrepreneurs are known to take initiative and act through self-motivation (Omer Attali & Yemini, 2017;Wilson Kasule et al, 2015). They are enthusiastic and energetic (Leffler, 2009) instigators (Hanson, 2017) who show an "operational translation of symbols and behaviors into actions" (Eyal & Kark, 2004, pp.…”
Section: Social Value-oriented Teacher Entrepreneursmentioning
confidence: 99%
“…Opportunity-Minded. An entrepreneurial teacher is able to explore opportunities related to their work (Wilson Kasule et al, 2015), meaning they are continuously "proactively seeking and being ready to seize opportunities" (Borasi & Finnigan, 2010, p. 4). Opportunities are often in the form of problems in the classroom or educational system which teacher entrepreneurs believe can be resolved (van der Heijden et al, 2015).…”
Section: Social Value-oriented Teacher Entrepreneursmentioning
confidence: 99%
“…This suggests that Ugandan teachers' abilities and constraints in using particular pedagogical approaches, such as those intended by the thematic curriculum, are not simply produced by external contextual influences, but are shaped significantly by their epistemological beliefs. This may offer insights into the lack of change in classroom pedagogy in response to Ugandan initiatives in policy and curriculum design (Kasule et al, 2015) There is therefore is an explicit complementarity between Ugandan's policies to develop an inclusive education system, (U.P. E., (1997); People with Disability Act ( 2006)), and the pedagogical assumptions of the thematic curriculum (NCDC, 2006).…”
Section: Teachers' Epistemological Beliefsmentioning
confidence: 99%